Service Innovation for Customer Satisfaction of Telecommunication Companies - Shinta Devi Lukitasari (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2020)
Customer perception is important in the company's business sustainability. In today's competitive global market situation, customers are always looking for services that have more value to meet their needs. Innovation becomes important to differentiate service values ​​in customer perceptions. This paper presents several survey papers which state the significant relationship between the innovation of telecommunications companies and their customers' satisfaction and loyalty. The influence factors considered by customers and aggressively affect their satisfaction also explained in previous surveys. Several innovations have also been carried out by various researchers to improve customer perceptions through excellent customer experience when interacting with customer relationship management. This paper also presents the novel method of developing value-added services for telecommunications companies and the development service roadmap that accurately predicts the successful implementation of an innovation into the market. Further research can utilize the above studies to develop services in other aspects of customer experience on telecommunications services.